2023
DOI: 10.1155/2023/8345333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional Cataract Surgery and Femtosecond Laser‐Assisted Cataract Surgery on Bruch’s Membrane Opening‐Minimum Rim Width, Retinal Nerve Fiber Layer, and Macular Thickness

Abstract: Purpose. To evaluate the effect of conventional cataract surgery (CCS) and femtosecond laser-assisted cataract surgery (FLACS) on Bruch’s membrane opening-minimum rim width (BMO-MRW), peripapillary retinal nerve fiber layer thickness (RNFL), and macular thickness (MT) using spectral-domain optical coherence tomography (SD-OCT). Methods. BMO-MRW, RNFL, and MT were measured using SD-OCT preoperatively, 1 month and 6 months after surgery in both CCS and FLACS groups. Differences between preoperative and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Moreover, another study has reported lower postoperative macular thickness in the FLACS group than in the CCS group. Specifically, although the FLACS group showed lower preoperative macular thickness, the CCS group showed a larger mean increase in macular thickness, which further accentuates the between-group difference in postoperative macular thickness [ 18 ]. These previous reports are consistent with our findings, indicating that FLACS has a lesser impact on the retina than CCS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study has reported lower postoperative macular thickness in the FLACS group than in the CCS group. Specifically, although the FLACS group showed lower preoperative macular thickness, the CCS group showed a larger mean increase in macular thickness, which further accentuates the between-group difference in postoperative macular thickness [ 18 ]. These previous reports are consistent with our findings, indicating that FLACS has a lesser impact on the retina than CCS.…”
Section: Discussionmentioning
confidence: 99%